The Influence Of Competence On Employee Performance Moderated By Leadership At MTS Nurul Falah Kemuning And MTS Nurul Falah Gosali - Mujiburrohman, Mujiburrohman; Ramdansyah, Agus David; Imron , Ali (Sahabat Publikasi, 2025)
This study aims to thoroughly examine the relationship between work motivation and employee competence on job performance, while also exploring the role of leadership as a moderating variable in this relationship. The research focuses on how individual internal factors—namely motivation and competence—contribute to achieving optimal performance, and the extent to which leadership can strengthen the influence of these two variables. A quantitative approach with a descriptive and explanatory design was employed to provide a comprehensive overview and to test the causal relationships among variables. The research subjects included all employees of MTS Nurul Falah Kemuning and MTS Nurul Falah Gosali, totaling 88 individuals. A census sampling technique (total sampling) was applied, in which the entire population was used as the sample. Data collection and analysis were conducted using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, utilizing SmartPLS software to ensure the accuracy and reliability of the analysis. The findings reveal that work motivation has a positive and significant effect on employee performance, indicating that enthusiasm and intrinsic drive play a crucial role in enhancing productivity and achieving performance targets. Similarly, employee competence was found to have a significant positive influence on performance, suggesting that skills, knowledge, and technical abilities are essential for effective task execution. The moderation analysis further indicates that leadership enhances the impact of both motivation and competence on performance, although the moderating effect is relatively modest. Overall, the study underscores that performance improvement is not solely dependent on individual factors, but also significantly influenced by the quality of leadership within the organizational environment.